Are takaful operators at the sympathy of retakaful operators in Malaysia? - Htay, Sheila Nu Nu; Hamat , Mustapha; Wan Ismail, Wan Zamri; Salman, Syed Ahmed (Medwell Publishing, 2014)
The concept of insurance is novel and excellent, since it tries to help the participants in the case of misfortune. It is prohibited from the Islamic aspect because the practice of insurance involves interest, uncertainty and gambling. Takaful has been introduced as an alternative to insurance and at the same time, Retakaful has emerged as an alternative to reinsurance. Unfortunately, due to the limited number of Retakaful operators and over reliance of the Takaful operators on the Retakaful operators seem to create Takaful operators helpless except to follow the demand of the Retakaful operators. In addition, they have more bargaining power than Takaful operators. This study provides the evidence that higher proportion of general Takaful contribution goes for Retakaful expenses. Thus, it is time for the Takaful operators to realize that they are at the sympathy of Retakaful operators and the former one needs to find an alternative Retakful method, for example Retakaful pool method, apart from the traditional way of ceding their risks through Retakaful operators.